Growth and survival of marine sponges, Stylissa massa (Carter, 1887) and Liosina paradoxa (Thiele, 1899) in sea and land based culture systems - Kiruba Sankar, R.; Chadha, N. K.; Dam Roy, S.; Banerjee, Paramita; Saharan, Neelam; Krishnan, P. (Indian Journal of Fisheries, 2016)
Two species of marine sponges Stylissa massa and Liosina paradoxa were cultured in cages (in situ) and in land based aquaria (ex situ) over a period of 120 days. Growth and survival were evaluated using four substrates viz., tile, block, coral rock and rope) under both in situ and ex situ conditions. L. paradoxa in cages recorded significant increase (p<0.05) on day 90 i.e., by 70% compared to initial volume whereas at 120 days there was a significant (p<0.05) decrease (54.22%).Â S. massa showed significant increase (p<0.05) in growth by 95.6% at 120 days compared to initial volume. Negative growth was recorded in S. massa under aquarium conditions while L. paradoxa recorded good growth as well as survival and performed exceptionally well in aquarium during the entire experimental period of 120 days. In cages, 90.62% survival was recorded for S. massa in 120 days. Among the different substrates used, coral rocks gave 100% survival whereas other substrates such as tiles, blocks and ropes showed 87.5% survival. Under aquarium conditions, S. massa showed overall survival of 81.25% and among the different substrates, 100% survival was obtained with coral rocks, 87.5% with blocks, 75% with ropes and the lowest survival of 62.5% was recorded with tiles.